Integration of the social dimension in urban wastelands reconversion projects : case of the Guelma railway station, Algeria - Ghedjati, Meryem; Debache- Benzagouta, Samira (Penerbit Universiti Kebangsaan Malaysia, 2021)
The railway station of Guelma (city located in the Northeast of Algeria) is an imposing building, built by the French colonization, which is closed now after so many years of prosperity. The development of the city and the urban sprawl have meant that after having been located for a long time on the periphery, this station now occupies a central position, where the city is now made. However, the future of this station is so far unclear since it will no longer be operational, given that the new Guelma’s railway station will be located on the outskirts of the city. What would be the fate of this architectural good left to itself? By preserving the memory of the station by offering it a new permanent use, this architectural jewel with its fallow site is a real opportunity for urban regeneration for the city. Therefore, the purpose of this paper is to try to give new life to Guelma station, through a new global approach that would channel the useful and sustainable reuse of the site from its immediate environment and the current executive context. The questionnaire was used as an investigative tool intended for residents living near the station, in total, 40 respondents have been surveyed, to find out their opinions and expectations relating to the future of this lost part of the city. The data from the study were descriptively analyzed, using percentages. Results revealed that the inhabitants are aware of the importance of the reconquest of the station, which will constitute for them a real opportunity for urban and economic development for the region. A reconquest that wants to be sustainable by adopting a socio-spatial approach, which will integrate socio-economic and environmental aspects.